Effect of Tribological Layer Formation on Wear Resistance of PI- and PEI-Based Nanocomposites in Point and Line Contacts - Sergey V. Panin; Jiangkun Luo; Dmitry G. Buslovich; Vladislav O. Alexenko; Lyudmila A. Kornienko; Anton V. Byakov; Artur R. Shugurov; Konstantin S. Panin; Filippo Berto (Applied Sciences, 2023)
The tribological performance of both PI- and PEI-based nanocomposites, reinforced with chopped carbon fibers (CCF) and additionally loaded with halloysite nanotubes (HNTs) as well as carbon nanotubes (CNT), was investigated. Metal (GCr15 steel) counterparts were utilized in the point (“ball-on-disk”) and linear (“block-on-ring”) tribological contacts. In the point contact, the PEI/10CCF/1HNT nanocomposite was characterized by the maximum wear resistance and the absence of microabrasive damage of the steel counterpart (Ra = 0.02 µm). The effect of tribological layer formation through creep and mixing mechanisms was proposed to make it possible to protect (shield) the contacting surfaces. In the linear contact at the higher Ra counterpart roughness of 0.2 µm, the tribological layer was formed on both PI- and PEI-based nanocomposites. This was governed by the development of both creep and mixing processes under the cyclic action of the tangential load transmitted from the sliding counterpart and being localized on the wear track. Due to the combination of both higher manufacturability and lower cost, the PEI-based nanocomposite loaded with CCFs and HNTs is a promising inexpensive material for fabricating components of metal–polymer friction units.